Evaluation, Selection and Simulation of Maximum Power Point Tracking Algorithm for LEO Satellite Electrical Power System - Zahid, Humayun (International Conference on Energy Conservation and Efficiency (Online), 2024)
Energy is a premium resource in the world of on-board satellite communications. Most of the energy in space is generated from solar panels. But unfortunately, solar energy isn't always available during different phases of a satellite's orbit/trajectory. As a result, the on-board batteries kick-in during solar eclipse and provide the required power to satellite subsystems. Thus it is paramount that the batteries be replenished quickly and efficiently during the sun-lit phase. The satellite Electrical Power Sub-system (EPS) is responsible for providing, managing and replenishing this energy. Methods like Direct Energy Transfer (DET) and Maximum Power Point Tracking (MPPT) are used to optimally interface/manage the EPS load. This work gauges the merits and demerits of satellite EPS operation using DET and MPPT for the proposed LEO orbital configurations and the one best suited for the considered mission profile is selected. A mission specific MATLAB/Simulink-based model is also developed to test and evaluate the performance of various MPPT techniques (e.g., P&O, IC, FOCV, FSCC, etc.) for our orbital/load requirements. Furthermore, performance comparison of these techniques is also evaluated based on a-priori mission requirements such as prior tuning, dynamic and steady-state tracking, algorithm/hardware complexity and sensor requirements. Based on these performance parameters and the simulation results (i.e. steady-state voltage fluctuations), P&O MPPT technique is selected for our rapidly varying satellite orbital conditions.